2019
DOI: 10.1002/jgm.3094
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of life cycle defective adenovirus mutants for production of adeno‐associated virus vectors

Abstract: Background Adeno‐associated virus‐based vectors are efficient and safe drug candidates for different in vivo gene therapy applications. With increasing numbers of clinical studies based on AAV2 vectors that include not only rare, but also common diseases as a therapeutic target, there is an increased demand for the development of improved production technologies. Methods In the present study, we compared two life cycle defective adenovirus mutants as helper viruses for AAV2 vector production. They had deletion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 52 publications
(110 reference statements)
0
5
0
Order By: Relevance
“…As discussed previously, Krüger-Haag et al showed that an adenovirus helper deleted of the 100K gene was unable to efficiently promote rep/cap amplification from an AAV packaging cell line 20 . Interestingly, the same authors showed that an adenovirus deleted of the pre-terminal protein (pTP) was fully capable of inducing rep/cap amplification and rAAV production.…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…As discussed previously, Krüger-Haag et al showed that an adenovirus helper deleted of the 100K gene was unable to efficiently promote rep/cap amplification from an AAV packaging cell line 20 . Interestingly, the same authors showed that an adenovirus deleted of the pre-terminal protein (pTP) was fully capable of inducing rep/cap amplification and rAAV production.…”
Section: Resultsmentioning
confidence: 81%
“…As Kruger-Haag et al showed that while the 100K-deleted adenovirus was unable to support rAAV production, an observation consistent with TESSA-E1 during MLP repression, the pTP-deleted adenovirus successfully promoted rep/cap DNA amplification despite this pTP-mutant being unable to undergo DNA replication with concomitant poor MLP activation and only limited 22/33K 20 . This apparently contradictory finding led us to hypothesize that, perhaps, sufficient 22/33K proteins are expressed from its internal L4P but can be titrated away from the CARE-amplification process by large amounts of replicating adenovirus genomes within the cell.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Empty adenovirus vectors (Ad.null) and vectors encoding SOD2 (Ad.SOD2) were purchased from Shanghai Liangtai Biotechnology Company, and transductions were performed as previously described ( 21 ). To yield the adenovirus, the linearized construct DNA was transfected into 293 cells (American Type Culture Collection) using Lipofectamine ® 2000 (Invitrogen; Thermo Fisher Scientific, Inc.), according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%